Detection of SARMs in doping control analysis - Thevis, Mario; Schänzer, Wilhelm (Molecular and cellular endocrinology, 2018)
The class of selective androgen receptor modulators (SARMs) has been the subject of intense and dedicated clinical research over the past two decades. Potential therapeutic applications of SARMs are manifold and focus particularly on the treatment of conditions manifesting in muscle loss such as general sarcopenia, cancer-associated cachexia, muscular dystrophy, etc. Consequently, based on the substantial muscle- and bone-anabolic properties of SARMs, these agents constitute substances with significant potential for misuse in sport and have therefore been added to the Word Anti-Doping Agency's (WADA's) Prohibited List in 2008. Since then, numerous adverse analytical findings have been reported for various different SARMs, which has underlined the importance of proactive and preventive anti-doping measures concerning emerging drugs such as these anabolic agents, which have evidently been misused in sport despite the fact that none of these SARMs has yet received full clinical approval. In this review, analytical data on SARMs generated in the context of research conducted for sports drug testing purposes are summarized and state-of-the-art test methods aiming at intact drugs as well as diagnostic urinary metabolites are discussed. Doping control analytical approaches predominantly rely on chromatography hyphenated to mass spectrometry, which have allowed for appropriately covering the considerable variety of pharmacophores present in SARMs such as the non-steroidal representatives ACP-105, BMS-564929, GLPG0492 (DT-200), LG-121071, LGD-2226, LGD-4033/VK 5211, ostarine/enobosarm, RAD-140, S-40503, etc. as well as steroidal compounds such as MK-0773 and YK-11. •Comprehensive review of mass spectrometric data generated from SARMs for doping control purposes.•Compilation of structural features of SARMs with various different pharmacophores.•Discussion of dissociation pathways as observed in product ion mass spectra of SARMs and corresponding metabolites.